Spleen Perfusion as an Index of Gender Impact on Sympathetic Nervous System Response to Exercise - Lanfranchi, Francesco; D'Amico, Francesca; Raffa, Stefano; Pennone, Michele; Donegani, Maria Isabella; Miceli, Alberto; Chiola, Silvia; Maggio, Sara; Delucchi, Carlo; Cossu, Vanessa; Morbelli, Silvia; Bauckneht, Matteo; et al. (Frontiers in Physiology, 2021)
Objective: Sympathetic nervous system (SNS) reaction to exercise is gender dependent. Nevertheless, clinically applicable methods to identify this difference are still missing. An organ largely sensitive to SNS is the spleen whose response to exercise can be easily evaluated, being included in the field of view of myocardial perfusion imaging (MPI). Here, we aimed to verify whether gender interferes with the spleen perfusion and its response to exercise. Methods: To this purpose, we evaluated 286 original scans of consecutive patients submitted to MPI in the course of 2019. Our standard procedure implies a single-day stress-rest sequence with a gap of ≥2 hours between the administrations of 180 and 500 MBq of 99mTc-Sestamibi, respectively. Imaging is performed 30 minutes after radiotracer administration, with scan duration set at 25 and 35 seconds per view, respectively. Non-gated scans were reconstructed with the filtered back-projection method. A volume of interest was drawn on the spleen and heart to estimate the dose-normalized average counting rate that was expressed in normalized counts per seconds (NCPS). Results: In all subjects submitted to exercise MPI (n=228), NCPS were higher during stress than at rest (3.52±2.03 vs 2.78±2.07, respectively; p<0.01). This effect was not detected in the 58 patients submitted to dipyridamole-stress. The response to exercise selectively involved the spleen, since NCPS in heart were unchanged irrespective of the used stressor. This same response was dependent upon gender, indeed spleen NCPS during stress were significantly higher in the 75 females than in the 153 males (3.86±1.8 vs 3.23±1.6, respectively, p<0.01). Again, this variance was not reproduced by heart. Finally, spleen NCPS were lower in the 173 patients with myocardial reversible perfusion defects (summed difference score ≥3) than in the remaining 55, despite similar values of rate pressure product at tracer injection. Conclusion: Exercise interference on spleen perfusion can be detected during MPI. This effect is dependent upon gender and ischemia confirming the high sensitivity of this organ to SNS activation.